Genetic Diversity in Ber (Ziziphus mauritiana L.) Accession Collected from Haryana and Rajasthan (Indian Journal of Arid Horticulture, 2025)
The Indian jujube, commonly known as ber (Ziziphus mauritiana Lamk.), is one of the important fruit crops of the hot arid regions in India. It forms an integral part of the lives of locals as a source of nutrition and for various other purposes (Krishna and Parashar, 2013). The tree is an example of an extremely drought-hardy species that can be grown in dryland areas and on degraded, eroded, gravelly, saline, and sodic wastelands.The jujube tree holds significant commercial importance due to the usefulness of almost all its parts (Krishna et al., 2016a). A wide range of variability exists in ber in India for various important characteristics, suggesting substantial scope for improvement. However, such genetic diversity needs to be identified and conserved, as plant breeders require genetic variation (genotypes) for crop improvement (Trivedi et al., 2013). Furthermore, a reduction in genetic variability makes a crop increasingly vulnerable to diseases and adverse climatic changes (Saran et al., 2006). Therefore, proper attention to the exploration, collection, conservation, and characterization of genetic resources of ber is the need of the hour, especially in view of the dynamic market demand for improved varieties and the necessity for developing climate-resilient cultivars.Most of the present-day commercial cultivars have been developed through seedling selection by farmers, based on their economic traits (Awasthi and More, 2009). Therefore, to identify suitable genotypes with desirable characteristics, a survey followed by the collection of promising genotypes was conducted in selected districts of Haryana and Rajasthan.
Keywords: jujube; commercial; exploration